Pitfalls, ditches and a wall: territorial defence strategies of the Bamun of Foumban, Cameroon. Issue 3 (3rd July 2018) - Nsangou, Jacques Aymeric
ABSTRACT: When the Bamun arrived in the late sixteenth century in the Noun Division of the western part of Cameroon, many sedentary farming communities shared the lands between the Mbam and Noun Rivers. In order to control and preserve this territory, the Bamun used different strategies. This paper discusses how, using oral and historical sources, it has been possible to reconstruct the evolution of their concepts of acquisition and conservation of territory. This, in turn, allows a chronology to be established for the implementation of the structures resulting from these strategies. Archaeological surveys and targeted test-pitting have also located and studied this defensive architecture. This research has revealed the serious state of deterioration of such structures and raises the question of their preservation in order to enhance the material cultural heritage of this region of Cameroon.